1984
DOI: 10.1002/zoo.1430030205
|View full text |Cite
|
Sign up to set email alerts
|

Comparative gross anatomy of ratites

Abstract: The four most common ratites kept in captivity, emus, rheas, ostriches, and cassowaries, share similar musculoskeletal features based on their common evolution to a flightless form. However, they differ in body size and coloration, wing size relative to entire body size, extent of leg feathering, and number of toes. During necropsies we observed the differences among the birds, which include the shape of tongue and tonsils, a tracheal cleft found only in emus, varied shapes of the thymus, spleen, bursa of Fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
5

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 3 publications
4
48
0
5
Order By: Relevance
“…This study confirmed the basic observation by previous authors (Faraggiana 1933, Cho et al 1984, Fowler 1991, Bezuidenhout 1999, Rodrigues 2012) that the rhea tongue is dark coloured small, triangular or V-shaped, and has a flat rigid appearance. Although flat, the surface of the rhea tongue has a spotted appearance.…”
Section: Floor Of the Oropharynxsupporting
confidence: 92%
“…This study confirmed the basic observation by previous authors (Faraggiana 1933, Cho et al 1984, Fowler 1991, Bezuidenhout 1999, Rodrigues 2012) that the rhea tongue is dark coloured small, triangular or V-shaped, and has a flat rigid appearance. Although flat, the surface of the rhea tongue has a spotted appearance.…”
Section: Floor Of the Oropharynxsupporting
confidence: 92%
“…In the model of continental vicariance, Rheas are nested within the group consisting of Kiwis, Cassowaries, and Emus as a sister group to Tinamous (figure 3B in Mitchell et al 2014). This would mean that their ''intermediate'' gastrointestinal anatomy and physiology evolved recently from among ancestors that otherwise gave rise to birds of comparatively simple gastrointestinal tracts (Emus and Cassowaries: Cho et al 1984;Tinamous: Chikilian and De Speroni 1996;Kiwis: Potter et al 2006) and digestive physiology (this study for Emus), and as a sister group to the only extant flighted ratites. In contrast, the phylogeny based on mitochondrial sequences suggests that after the divergence of Ostriches from the ancestral ratite lineage, Rheas diverged next, with a common ancestor for all remaining ratite taxa (figure 3C in Mitchell et al 2014).…”
Section: Discussionmentioning
confidence: 96%
“…These studies vary from gross morphological descriptions of the tongue of Rhea pennata (Orbigny, 1834) (Cho et al 1984), Casuarius casuarius (Linnaeus, 1758) (Gadow 1879;Pycraft 1900), S. camelus and D. novaehollandiae (Faraggiana 1933;Cho et al 1984;Bonga Tomlinson 2000) to macroscopic and microscopic studies of the tongue of S. camelus (Porchescu 2007;Jackowiak and Ludwig 2008;Tivane 2008;Guimarães et al 2009) and detailed studies (including light and scanning electron microscopy) of the tongue of D. novaehollandiae Soley 2009a, b, 2010b). In contrast, only minimal information on the morphology and function of the tongue (Owen 1835;Faraggiana 1933;Feder 1972;Bonga Tomlinson 2000;Gussekloo and Bout 2005;Santos et al 2011) and laryngeal mound (Owen 1835;Faraggiana 1933;Bonga Tomlinson 2000;Gussekloo and Bout 2005) of Rhea americana (Linnaeus, 1758) has been published.…”
Section: Introductionmentioning
confidence: 99%